The six‐spot‐step test – a new method for monitoring walking ability in patients with chronic inflammatory polyneuropathy. Issue 2 (8th June 2017) - Kreutzfeldt, Melissa; Jensen, Henrik B.; Ravnborg, Mads; Markvardsen, Lars H.; Andersen, Henning; Sindrup, Søren H.
Abstract: The aim of this study was to evaluate whether the six‐spot‐step test (SSST) is more suitable for monitoring walking ability in patients with chronic inflammatory polyneuropathy than the timed 25‐foot‐walking test (T25FW). In the SSST, participants have to walk as quickly as possible across a field measuring 1 × 5 m, while kicking blocks out of five circles on the floor. Sixty‐two patients and 61 controls performed the SSST and T25FW. Patients also performed the overall disability sumscore, INCAT sensory sumscore, Medical Research Council sumscore, and 9‐hole‐peg‐test. Twenty‐one patients treated with intravenous immunoglobulin (IVIG) every 4–6 weeks were tested prior to and 2–3 weeks after treatment and judged change in their own clinical condition using the patient global impression of change (PGIC) scale. In patients, SSST ranged from 5.7 to 26.8 s and T25FW ranged from 3.6 to 12.9 s. Intra‐class correlation between repeated tests was 0.97 for SSST and 0.95 for T25FW. Correlation with the additional tests was stronger for SSST than T25FW. In IVIG‐treated patients, the mean change in walking time was −2.3 s for SSST and −0.6 s for T25FW. The SSST showed larger responsiveness in terms of effect size, standardized response means, and relative efficiency. Both ambulation tests correlated moderately to PGIC. The SSST may be superior to the T25FW in terms of dynamic range, floor effect, and responsiveness which makes the SSST a possible alternative for monitoring walking ability in patients with chronic inflammatory polyneuropathy.